Lithium-ion Batteries - Rae Park, Chong (IntechOpen, 2010)
There have been numerous excellent books on LIBs based on various different viewpoints. But, there is little book available on the state of the art and future of next generation LIBs, particularly eventually for EVs and HEVs. This book is therefore planned to show the readers where we are standing on and where our R&Ds are directing at as much as possible. This does not mean that this book is only for the experts in this field. On the contrary this book is expected to be a good textbook for undergraduates and postgraduates who get interested in this field and hence need general overviews on the LIBs, especially for heavy duty applications including EVs or HEVs.